A nudge towards better lumbar puncture practice - Holland, C; Edmond, EC; Moore, C; Tobert, V; Klein, JC; Turner, M (Royal College of Physicians, 2020)
Background Despite a body of evidence demonstrating reduced incidence of post-lumbar puncture headache associated with pencil-point (vs bevelled-edge) needles, their use remains variable in the UK.